A7.8 DNA Demethylation in Salivary Gland Epithelial Cells from Patients with Primary Sjögren's Syndrome may be Ascribed to Infiltrating B Cells. (25th February 2013) - Renaudineau, Yves; Thabet, Yosra; Dantec, Christelle Le; Ghedira, Ibtissem; Devauchelle, Valérie; Cornec, Divi; Pers, Jacques-Olivier
Abstract : Background and Objectives: Sjögren's syndrome (SS) is an autoimmune exocrinopathy characterised by an epithelium injury surrounded by dense lymphocytic infiltrates composed of activated T and B cells. Present at the interface of genetic and environmental risk factors, epigenetic modifications are suspected to play a key role in SS. Accordingly, we decided to further characterise DNA methylation in SS. Materials and Methods: We tested, using a 5 methyl cytosine (5MeCyt) ELISA, global DNA methylation in long-term cultured salivary gland epithelial cells (SGEC), peripheral T cells and B cells from eight SS patients. DNA methylation/demethylation partners were assessed by real time quantitative PCR (DNA methyl transferase (DNMT)1, DNMT3a/b, PCNA, UHRF1, MBD2, MBD4, and Gadd45-alpha). Immunofluorescence was conducted on labial salivary gland biopsy. Co-culture experiments were performed associating the human salivary gland cell line (HSG) and B cells. Results: Global DNA methylation was reduced in SGEC from SS patients (5MeCyt: 36.3 ± 3.2% in SS versus 43.1 ± 3.3% in controls, P = 0.01), while no difference was observed in T and B cells. SGEC demethylation in SS patients was associated with a 7-fold decrease of DNMT1 and a 1.8-fold increase of Gadd45-alpha expression. The other DNA methylation/demethylation partners tested were not differently expressed when compared to controls. Interestingly, SGEC demethylation may be attributed to the B cell infiltrate as DNA methylation increased in salivary gland biopsy after rituximab (anti-CD20 antibody) treatment. Such hypothesis was confirmed using co-culture experiments (HSG cells and B cells) revealing an alteration of the PKC-delta/ERK/DNMT1 pathway. Finally, DNA methylation was associated with the overexpression of several SGEC genes such as ICAM-1 and human endogenous retrovirus (HERV). Conclusions: SGEC dysfunction in SS may be linked to epigenetic modifications and this tissue specific defect may be ascribed in part to infiltrating B cells. This observation opens new therapeutic perspectives in SS.